Propaganda religiosa y negocio editorial - Philippe Castellano (Cahiers de Civilisation Espagnole Contemporaine)
The letters sent between 1903 and 1910 by Dionisio Fierro Gasca, a monk and translator, to his publisher Gustavo Gili Roig, allows us to understand how a catalogue of religious works was made up. The letters state precisely the criteria needed to choose which foreign titles were to be translated and, depending on the readers to whom those books were intended, which material elements in the book production could promote its reception. The churchman also advised the publisher on advertising dealings and selling devices beside bookshops. Finally, his perfect knowledge of Latin America book market showed itself absolutely necessary to ensure the success of published works and the development of the publishing house.